EUFEMISME DAN DISFEMISME DALAM SPIEGEL ONLINE - Heti Kurniawati (LITERA, 2011)
This research aims to describe the forms of grammatical units of euphemisms and dysphemisms, and the backgrounds of euphemisms and dysphemisms uses in Spiegel Online. The data were collected through reading and note taking. The resultsshow that the forms of grammatical units of euphemisms and dysphemisms in Spiegel Online consist of words, phrases and sentences. The backgrounds of the use of euphemisms in Spiegel Online are: 1) to avoid the use of words which can cause panic or anxiety; 2) to mitigate speech; 3) to diminish or tone down a painful evocation or tragedy; 4) to engage in diplomacy or rhetoric purposes; 5) to replace forbidden words, taboos, vulgar or negative imaged-words; 6) to hide something; 7) to respect or appreciate others; and 8) to tease or criticize others smoothly. Thebackgrounds of the use of dysphemisms in Spiegel Online are: 1) to constitute taboos, improper, or immoral matters; 2) to show one’s dislike or disagreement; 3) to give negative description; 4) to show anger or irritation; 5) to scold; 6) to show disrespect;7) to mock; 8) to exaggerate or overstate; 9) to criticize; and 10) to show trivial matters.